Beyond ordinal scales: making animal welfare count in policy analysis - Fischer, Bob (Frontiers in Veterinary Science, 2025)
Animal welfare is typically assessed using ordinal scales. That is, standard welfare assessment tools rank conditions relative to one another without claiming that one condition is worse than another by some specific magnitude. However, there are some practical purposes for which ordinal scales are insufficient, such as accounting for animal welfare in policy analysis. Here, I argue that insofar as we want standard policy analysis tools to capture impacts on animal welfare in a way that is scope sensitive—that is, in a way that properly recognizes differences in the number of animals affected—we need ways of representing animal welfare on ratio scales, not merely ordinal ones. Then, I briefly explain how some economists, who play important roles in policy analysis, are beginning to do this without the assistance of animal welfare scientists, veterinarians, and others. So, this perspective article serves as a call to those stakeholders, inviting them to collaborate with economists and policy analysts to improve existing methods or develop better alternatives that meet current needs.